Dickens and demolition - Hofer-Robinson, Joanna (Edinburgh University Press, 2018)
Dickens and Demolition examines how tropes, characters, or extracts from Dickens' fiction were repurposed as a portable terminology in arguments for large-scale demolition and redevelopment projects in London during his lifetime.
Title from publisher's bibliographic system (viewed on 03 May 2021)
Keywords: Novelists; English; Urbanization; City planning